The use of magnetic resonance imaging for the assessment of distal limb wounds in horses: A pilot study. (20th May 2019) - Sherlock, C.; Fairburn, A.; Lawson, A.; Mair, T.
Summary: The utility of magnetic resonance (MR) imaging in the evaluation of equine solar foot penetrations is well established. The objective of this pilot study was to evaluate the utility of MR imaging in assessment of equine distal limb wounds excluding solar penetrations. Low‐field MR images of 23 horses that had previously sustained distal limb wounds were reviewed in consensus by two ECVDI diplomats. Structures (bone; synovial structure; subcutaneous tissue and skin; and ligament/tendon) were identified as normal or abnormal on MR images, radiographs and ultrasound images and reports. All abnormalities were described. The presence of artefacts and their effect on image interpretation were also noted for each modality. Comparisons were made between imaging modalities, and it was noted if MR imaging influenced case management. Abnormalities of the bone were identified in 26% of horses on MR images and 17% of horses on radiographs; there were no osseous abnormalities identified on radiographs that were not identified on MR images, and additional features and better characterisation of lesions were noted on MR images. Tendon/ligament abnormalities were identified in 57% horses on MR and 47% of horses on ultrasound images. Magnetic susceptibility artefacts compromised MR image interpretation in 17% of horses. MR imaging of equine distal limb wounds allowed identification of both osseous and tendon/ligament abnormalities in more cases than either radiography or ultrasonography, and altered case management in 20/23 horses. Although MR imaging should not replace conventional imaging, this study highlights that MR imaging of equine distal limb wounds can yield information not detected on conventional imaging which may direct treatment and affect prognostication.